A Shelf-Life Assessment of Sterilized Surgical Instruments Stored Under Controlled Conditions: A Comparative Study of a Single vs. Double Self-Sealing Pouch - Stefano Cavalli; Chiara Caterino; Francesca Paola Nocera; Francesca Pizzano; Rossana Schena; Federica Aragosa; Sinem Arslan; Giovanni Della Valle; Luisa De Martino; Gerardo Fatone (Veterinary Sciences, 2025)
(1) Background: postoperative surgical-site infections are a significant complication in small-animal surgical procedures, with detected rates ranging from 0.8% to 18.1%, depending on the type of surgery. The sterilization process of surgical instruments is a crucial factor in infection control, but the shelf life of surgical instruments and the best packaging method are not precisely defined due to the multiple variables that influence them. This study aimed to assess the shelf life of surgical instruments stored under controlled environmental conditions in a veterinary hospital and compare two packaging methods: using a self-sealing single pouch versus a self-sealing double pouch. (2) Methods: a sample of 400 non-sterile screws was divided into three groups: Group 1 (175 screws in single pouches), Group 2 (175 screws in double pouches), and Group 3 (50 non-sterile screws as a control group to verify the microbial culture efficiency). Microbiological tests were conducted at 1, 7, 15, 30, 60, 182, and 390 days post-sterilization. (3) Results: no bacterial growth was detected on screws packaged in single and double pouches up to 182 days. However, after 390 days, bacterial growth was observed in one screw packaged in a single pouch. In Group 3, only two screws turned out to be bacteriologically positive. (4) Conclusions: no statistical difference was found between the two groups; however, the detection of a single positive screw in the single-pouch group raised a potential clinical consideration, suggesting the need for further studies based on events and time.